The Connotative Meanings In “The Internship” Movie’s Dialogue: A Semantics Study - Jayana, I Made Mei (Udayana Journal of Social Sciences and Humanities; Vol 6 No 1 (2022): UJoSSH, February 2022, 2022)
The aims of this study are to describe and analyze connotative meanings of the internship movie’s dialogue. The researcher divides the data into two parts which are primary and secondary data. The primary data consists of the movies and the script were taken from the internet.  The method used in this study is qualitative descriptive and documentation technique. The main theory that the researcher used is the theory of semantics proposed by leech (1991). The result of this study shows that the connotative meaning of the internship movie’s dialogue consists of three types of connotative meanings both positive, negative and neutral connotations. Furthermore, this study shows that the word or the phrase selected and used by the characters in the movie depended on the condition or situation and with who they are talking to.